The Effect of Using Whispering Technique and Jigsaw Technique in Teaching English Vocabulary in the Fourth Grade of the Elementary School - Nurcahaya Sihombing; Erika Sinambela; Lastri Wahyuni Manurung (Sean Institute, 2022)
This research presented a report on using the Whispering Technique and Jigsaw Technique in teaching English vocabulary in the fourth grade the Elementary School. The objectives are to find out the effect of using the Whispering technique and Jigsaw technique in English vocabulary of students and which method is the most effective. It was by using experimental quantitative research. The subject of this study was the fourth grade of SD N 178064 consist of 32 students and the fourth grade of SD N 175798 consist of 16 students as the sample. They were divided into three groups. The first and the second group are Experimental Group and the third is Control Group. They were taught by using Whispering technique and Jigsaw technique in English vocabulary of the students, while the third group (Control Group) was taught without using Whispering technique and Jigsaw technique. The technique for data analysis is quantitative research. In analyzing the data, the mean of thestudents' pre-test in experimental group 1 (Whispering technique) is 60,25 and the mean of the post-test in experimental group 1 is 84,875. The mean of the students score for pre-test in experimental group 2 (Jigsaw technique) is 58,5 and the mean of the students score for post-test in experimental group 2 is 84,75. The mean for pre-test in control group is 47,25 and the mean for post-test in control group is 55,75. The conclusion is that the using of Whispering technique and Jigsaw technique are significantly affect the students in teaching English vocabulary. Whispering technique is the most effective one in teaching English vocabulary for students than Jigsaw technique especially for elementary school. It is suggested that teachers should apply these techniques to improve students in English vocabulary.